METAFORA DAN METONIMIA GELOMBANG DEWI LESTARI DAN KELAYAKANNYA SEBAGAI BAHAN AJAR SMA - Laudia Riska Umami; Kahfie Nazaruddin (FKIP Universitas Lampung, 2016)
This research aimed to describe metaphor and metonymy in Dewi Lestaris novel Gelombang and its eligibility as a teaching material in Senior High Schools. The method used in this study was descriptive qualitative method. The research found that there is a dominative number of metaphor (widely meaning) with 154 data which consist 54 data of metaphors (narrowly meaning), and 100 data of similes. Meanwhile, there are 49 data which consisted of 23 data of metonymies. Besides, there are synechdoches which consisted of 14 data of pars prototo and 12 data of totem proparte. These data were analyzed based on vehicle and tenor. Thus, metaphors and metonymies in Gelombang are suitable to be used as a literary teaching material for Senior High Schools especially in literary of bahasa Indonesia subject for XII graders because it complies the qualifications of choosing material for teaching.Penelitian ini bertujuan untuk mendeskripsikan metafora dan metonimia Gelombang karya Dewi Lestari dan kelayakannya sebagai bahan ajar sastra di SMA. Metode yang digunakan adalah metode deskriptif kualitatif. Hasil penelitian ini diketahui bahwa metafora (luas) sangat mendominasi dengan jumlah 154 data terdiri atas metafora (sempit) 54 data, dan simile 100 data, sedangkan metonimia jumlah keseluruhan 49 data terdiri atas metonimia 23 data, dan sinokdoke yang meliputi pars prototo 14 data dan totem proparte 12 data. Data tersebut dianalisis berdasarkan vehicle dan tenor. Adapun metafora dan metonimia dalam Gelombang layak dijadikan sebagai bahan ajar sastra di SMA khususnya mata pelajaran sastra Indonesia kelas XII, karena memenuhi syarat pemilihan bahan ajar.Kata kunci: metafora (luas) dan metonimia, vehicle dan tenor,kelayakan bahan ajar.